Sex differences in the toxicity of polyethylene glycol-coated gold nanoparticles in mice - Chen, Jie (Dove Medical Press, 2013)
Gold nanoparticles have received wide interest in disease diagnosis and therapy, but one of the important issues is their toxicological effects in vivo. Sex differences in the toxicity of gold nanoparticles are not clear. In this work, body weight, organ weight, hematology, and biochemistry were used to evaluate sex differences in immune response and liver and kidney damage. Pathology was used to observe the general toxicity of reproductive organs. The immune response was influenced significantly in female mice, with obvious changes in spleen and thymus index. Hematology results showed that male mice treated with 22.5 nm gold nanoparticles received more significant infection and inflammation than female mice. Meanwhile, the biochemistry results showed that 4.4 and 22.5 nm gold nanoparticles caused more significant liver damage in male mice than female mice, while 22.5, 29.3, and 36.1 nm gold nanoparticles caused more significant kidney damage in female mice than male mice. No significant toxicological response was found in the reproductive system for female or male mice. It was found that gold nanoparticles caused more serious liver toxicity and infection in male mice than female mice. These findings indicated that sex differences may be one of the important elements for in vivo toxicity of gold nanoparticles.